Overlap of Promoter Recognition Specificity of Stress Response Sigma Factors SigD and SigH in Corynebacterium glutamicum ATCC 13032 - Dostálová, Hana; Busche, Tobias; Holátko, Jiří; Rucká, Lenka; Štěpánek, Václav; Barvík, Ivan; Nešvera, Jan; Kalinowski, Jörn; Pátek, Miroslav (Frontiers in Microbiology, 2019)
Corynebacterium glutamicum ATCC 13032 harbors five sigma subunits of RNA polymerase belonging to Group IV, also called extracytoplasmic function (ECF) σ factors. These factors σC, σD, σE, σH and σM are mostly involved in stress responses. The role of σD consists in the control of cell wall integrity. The σD regulon is involved in the synthesis of components of the mycomembrane which is part of the cell wall in C. glutamicum. RNA sequencing of the transcriptome from a strain overexpressing the sigD gene provided 29 potential σD-controlled genes and enabled us to precisely localize their transcriptional start sites. Analysis of the respective promoters by both in vitro transcription and the in vivo two-plasmid assay confirmed that transcription of 11 of the tested genes is directly σD-dependent. The key sequence elements of all these promoters were found to be identical or closely similar to the motifs -35 GTAACA/G and -10 GAT. Surprisingly, nearly all of these σD-dependent promoters were also active to a much lower extent with σH in vivo and one (Pcg0607) also in vitro, although the known highly conserved consensus sequence of the σH-dependent promoters is different (-35 GGAAT/C and -10 GTT). In addition to the activity of σH at the σD-controlled promoters, we discovered separated or overlapping σA- or σB-regulated or σH-regulated promoters within the upstream region of 8 genes of the σD-regulon. We found that phenol in the cultivation medium acts as a stress factor inducing expression of some σD-dependent genes. Computer modeling revealed that σH binds to the promoter DNA in a similar manner as σD to the analogous promoter elements. The homology models together with mutational analysis showed that the key amino acids, alanine A60 in σD and lysine K53 in σH, bind to the second nucleotide within the respective -10 promoter elements (GAT and GTT, respectively). The presented data obtained by integrating in vivo, in vitro and in silico approaches demonstrate that most of the σD-controlled genes also belong to the σH-regulon and are also transcribed from the overlapping or closely located housekeeping (σA-regulated) and/or general stress (σB-regulated) promoters.